(untitled) (Journal of Atomic and Molecular Sciences, 2011)
We present relativistic calculations of the differential, integrated elastic, momentum transfer total cross sections and spin polarization parameters for positrons scattered from Gold atom using a simple optical model potential to represent interaction between positron and target atoms in the energy range 2.0-500eV. In the present calculation we employ a parameter-free model potential for the correlation polarization and absorption potential as devised for positron-atom scattering. The theoretical results are obtained from relativistic approach based on solving the Dirac equation using Hartree-Fock and Dirac-Fock wave functions.